“Wow! It’s Cool”: How Brand Coolness Affects the Customer Psychological Well-Being Through Brand Love and Brand Engagement - Attiq, Saman; Abdul Hamid, Abu Bakar; Khokhar, Munnawar Naz; Shah, Hassan Jalil; Shahzad, Amna (Frontiers in Psychology, 2022)
In this era of razor-edge competition, marketers strive to outperform their rivals by improving their brands. Increasing brand coolness may be the best way to do it. This study used a stimulus organism response (SOR) model by integration with brand attribution theory to conduct a cross sectional study using purposive sampling technique and surveying young consumers of smart gadgets in Pakistan. A total of 1,178 responses were received and analyzed by structural equation modeling. The results found a positive impact of brand coolness (stimulus) on brand love and brand engagement (both modeled as organism). Brand experience moderated these links. Brand love and brand engagement also mediated the relationship between brand coolness and consumer well-being and delight (both modeled as response). The findings suggest a very important contribution to theory and practice by testing unexploited outcomes of brand coolness. Especially, this study contributes to the consumer well-being literature, again an unexploited aspect of marketing literature. Despite the uniqueness of the findings, the cross sectional design of this study remains a major limitation. Future research may supplement the findings with the help of longitudinal studies. Marketers and practitioners may benefit from this study by improving the coolness of their brands so they may not only increase consumer engagement with the brand but they will also make consumers happy with their brands.